THE ANALYSIS OF INTENSE-DEFORMED MONOLITHIC CONCRETE STRIP STATE OF UNDERGROUND STRUCTURES OF NONCIRCULAR OUTLINE - Maria Aleksandrovna Bauer (International Journal of Advanced Studies, 2017)
The research results of intense deformed state (IDS) of the crepe and soil massif of un-derground structures having a non-circular outline with a depth of laying up to 50 m in unstable al-luvial rocks with dumps from 0.3 to 0.7 m are presented. The study was carried out by means of modeling the IDS of the soil massif and the hardening concrete of the monolithic support, erected after slaughter moving. To implement the proposed technological solutions ensuring the fixing of underground structures with monolithic concrete, it is necessary to use particularly fast solidifying compounds to exclude the use of temporary crepe. Based on the studies of a number of modifiers, various changes in mechanical properties of the most effective compositions have been established, which are used to simulate the concrete crepe of structures with time-varying characteristics.